Ecosystem state assessment after more than 100 years since planting for dune consolidation. Issue 7 (21st June 2021) - Bonari, Gianmaria; Padullés Cubino, Josep; Sarmati, Simona; Landi, Marco; Zerbe, Stefan; Marcenò, Corrado; Scoppola, Anna; Angiolini, Claudia
Abstract : The assessment of the ecosystem state is fundamental to understand the success of ecological rehabilitation, especially in the long term. We aim to evaluate the rehabilitation success of a unique Mediterranean dune system site along the Tyrrhenian coast of Italy which underwent a dune consolidation intervention and species planting at the beginning of the twentieth century after the destruction of the natural ecosystem. We used three nearby non‐rehabilitated protected coastal sites with different degrees of disturbance as reference sites encompassing different potential rehabilitation outcomes of the target site. To assess the overall result of the intervention, we used several plant characteristics and measured taxonomic and functional beta‐diversity between all sites. We compared the proportions of typical and ruderal species of dune habitat types across sites. We further used the species–area relationship to examine if the number of observed species in our sites differed from the expected. Our analyses revealed that the rehabilitated site was taxonomically and functionally more similar to the least disturbed site. We suggest that plant characteristics arising from botanical inventories can be fruitfully used in rehabilitation assessment as they value the taxonomic and functional species diversity at the community scale. We conclude that plant characteristics compared across sites are useful tools in ecosystem state assessment if they reflect the ecological functions and conservation values of the natural ecosystems.